2011
DOI: 10.1007/s11113-011-9215-4
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Support, Gender, and Racial/Ethnic Disparities in Hypertension Among Older Adults

Abstract: Using data from the 2001 NHIS and the -2006 we examine how self-reporting a previous diagnosis of hypertension among adults aged 65? differs by race/ethnicity for men and women; we explore the extent to which disparities are driven by group differences in social risk factors, particularly social support and integration; and last, whether these relationships mimic patterns seen for measured hypertension at interview. Findings indicate that rates of ever-diagnosed hypertension in both samples are highest among b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…As for age, as individuals grew 10 years older, their average SBP increased as much as 5 mmHg. BP and the risks of hypertension have been studied using a cohort study [12] [24]. A 10-year interval was used to define the age cohorts; however, the results of this study suggest that the 10 year interval might be too large, the distribution within cohorts should not be ignored, and the age cohorts should be revised to get more precise evaluations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for age, as individuals grew 10 years older, their average SBP increased as much as 5 mmHg. BP and the risks of hypertension have been studied using a cohort study [12] [24]. A 10-year interval was used to define the age cohorts; however, the results of this study suggest that the 10 year interval might be too large, the distribution within cohorts should not be ignored, and the age cohorts should be revised to get more precise evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Joffres et al [22] [23] pointed out that there were large differences between the distributions of SBP among Kenyan nomads and London civil servants, with the levels of the former much lower than the levels of the latter. It has also been suggested that race, genetic and environmental factors, and health administrative and practice patterns are important determinants of BP [4] [10] [24]. Therefore, it is necessary to evaluate the BP data by country.…”
Section: Introductionmentioning
confidence: 99%
“…Race, genetic and environmental factors, and health administrative activities are important factors for BP [7] [23] [24]. For example, Rose [25] compared the distribution of SBP in Kenyan nomads and London civil servants, and found that the former was much lower than the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BP levels were strongly affected by various factors such as the age, gender, health conditions, and lifestyles of the individuals. Race, genetic and environmental factors, and health administrative activities are also important factors for BP [17] [18] [19]. However, the methods used to adjust for the effects of individual characteristics in the various studies are not clear.…”
Section: Introductionmentioning
confidence: 99%